Design and Build Mail Server Systems Using Zimbra 8.8.15 and Antispam on Proxmox Mail Gateway 5.2: Design and Build Mail Server Systems Using Zimbra 8.8.15 and Antispam on Proxmox Mail Gateway 5.2 - Ahmad Yannuri; M. Iwan Wahyuddin; Andrianingsih Andrianingsih (Institute of Computer Science (IOCS), 2020)
E-Mail or electronic mail media currently continues to grow and its users are increasing. However, the comfort and security of communicating via e-mail is now greatly reduced. One reason for the reduced level of security and comfort in using e-mail is spam. Spam is e-mail that goes to the user's e-mail that the user has never requested and wanted, if the spam is left in the e-mail inbox it will create full storage capacity and can make the mail server down. To avoid and prevent the presence of spam e-mails, the Zimbra 8.8.15 mail server requires anti spam to be able to block spam e-mails that will enter. Anti spam that will be used is Proxmox Mail Gateway 5.2 as using the LDAP (Light Weight Directory Access Protocol) feature.